THE CONCEPT OF GREEN ECONOMY, ITS CURRENT ROLE, AND INTERNATIONAL PRACTICES - Daniyorova Mutabar Mamatazizovna (European Science Publishing, 2024)
This article explores the concept of the green economy, its current significance, and international practices. It highlights the principles of sustainability that underpin the green economy, focusing on key sectors such as renewable energy, energy efficiency, waste management, and sustainable agriculture. The study examines the global shift towards eco-friendly economic models, discussing their social, economic, and environmental benefits, as well as the challenges they face. Drawing on successful international practices, the article emphasizes the importance of innovation, education, and global collaboration in advancing the green economy.
Keywords: Green economy, sustainability, renewable energy, energy efficiency, circular economy, sustainable agriculture, green jobs, international practices, climate change, environmental protection.